Dose dependence of treatment-related adverse events for immune checkpoint inhibitor therapies: a model-based meta-analysis. (1st January 2020) - Shulgin, Boris; Kosinsky, Yuri; Omelchenko, Andrey; Chu, Lulu; Mugundu, Ganesh; Aksenov, Sergey; Pimentel, Rodrigo; DeYulia, Garrett; Kim, Geoffrey; Peskov, Kirill; Helmlinger, Gabriel
ABSTRACT: Programmed cell death-1 (PD-1) and/or cytotoxic T lymphocyte–associated antigen 4 (CTLA-4) immune checkpoint inhibitor (ICI) treatments are associated with adverse events (AEs), which may be dependent on ICI dose. Applying a model-based meta-analysis to evaluate safety data from published clinical trials from 2005 to 2018, we analyzed the dose/exposure dependence of ICI treatment-related AE (trAE) and immune-mediated AE (imAE) rates. Unlike with PD-1 inhibitor monotherapy, CTLA-4 inhibitor monotherapy exhibited a dose/exposure dependence on most AE types evaluated. Furthermore, combination therapy with PD-1 inhibitor significantly strengthened the dependence of trAE and imAE rates on CTLA-4 inhibitor dose/exposure.